Historiography of Studying of the Personality of N.N.Nepluev – the Teacher, the Philosopher and the Public Figure - Nadiya Kovalyova (Pedagogical Discourse, 2013)
Article is devoted to the historiography investigation of the outstanding public figure, the philosopher and teacher N.Nepluev’s activity. The most known and fundamental publications which studied the heritage, views and the main aspects of Nepluev’s life of are analyzed. Different views of authors on his outlook, pedagogical and public activity, activity of The Holy Cross Day Labor brotherhood are highlighted. Distinctive features of a modern historiography and historiography of the XIX century ending– XX century beginning are established.